Comparative Evaluation of Product and Service Solutions in the Context of Product-Service Systems and Technical Inheritance - Schneider, Jannik; Scheidel, Wieben; Wurst, Johanna; Mozgova, Iryna; Lachmayer, Roland

Quantification of the material-related environmental impact of topology-optimized multi-material components - Herrmann, Kevin; Bode, Behrend; Wurst, Johanna; Gembarski, Paul; Mozgova, Iryna; Lachmayer, Roland

Sustainability Assessment of Products manufactured by the Laser Powder Bed Fusion (LPBF) Process - Wurst, Johanna; Mozgova, Iryna; Lachmayer, Roland

Life cycle cost impact of maintenance networks for product-service system fleets - Schneider, Jannik; Mozgova, Iryna; Lachmayer, Roland

Procedure to Create an Automated Design Environment for Functional Assemblies - Altun, Osman; Kutay, Y; Mozgova, Iryna; Lachmayer, Roland

Ontology-Based Documentation of Quality Assurance Measures Using the Example of a Visual Inspection - Sheveleva, Tatyana; Herrmann, Kevin; Wawer, Max Leo; Kahra, Christoph; Nürnberger, Florian; Koepler, Oliver; Mozgova, Iryna; Lachmayer, Roland; Auer, Sören

Technical Inheritance as an Approach to Data-Driven Product Development - Lachmayer, Roland; Mozgova, Iryna (Design Methodology for Future Products)

Corporate Strategy Based Quantitative Assessment of Sustainability Indicators at the Example of a Laser Powder Bed Fusion Process - Wurst, Johanna; Schneider, Jannik; Ehlers, Tobias; Mozgova, Iryna; Lachmayer, Roland

Parametrization of a Hybrid Component Production Process Chain Based on Semantically Annotated Data. - Wawer, Max Leo; Sheveleva, Tatyana; Koepler, Oliver; Nürnberger, Florian; Mozgova, Iryna

Normalization Matrix for Sustainability Assessments Considering the Laser Powder Bed Fusion Process - Wurst, Johanna; Mozgova, Iryna; Lachmayer, Roland

Management of Research Field Data Within the Concept of Digital Twin - Dierend, Hauke; Altun, Osman; Mozgova, Iryna; Lachmayer, Roland

Morita theory for non-commutative noetherian schemes - Burban, Igor; Drozd, Yu. (Advances in Mathematics)
In this paper, we study equivalences between the categories of quasi–coherent sheaves on non–commutative noetherian schemes. In particular, we give a new proof of Căldăraru's conjecture about Morita equivalences of Azumaya algebras on noetherian schemes. Moreover, we derive necessary and sufficient condition for two reduced non–commutative curves to be Morita equivalent.

On elliptic solutions of the associative Yang-Baxter equation - Burban, Igor; Peruzzi, A. (Journal of Geometry and Physics)

The role of ICT for school leadership and management activities: an international comparison - Tulowitzki, Pierre; Gerick, Julia; Eickelmann, Birgit (International Journal of Educational Management)
Purpose Information and communication technologies (ICT) has an increasing impact on schools. School leaders play a key role in this context as drivers of innovation including those related to ICT. Against this background, the study presented in this article focuses on school leadership and management activities with ICT and related challenges. It sought to analyze how frequently German school principals use ICT compared to principals in other countries, what distinct clusters of German principals could be identified in terms of ICT usage and how principals viewed ICT in schools and related challenges. Design/methodology/approach A mixed-methods approach was chosen, using quantitative data from both the international comparative large-scale assessment study ICILS 2018 and the explorative qualitative data from Germany. For the international comparison, the school principal data sets of the 12 international participants of the International Computer and Information Literacy Study (ICILS) 2018 were taken into account: Chile, Denmark, Finland, France, Germany, Italy, Kazakhstan, Republic of Korea, Luxembourg, Portugal, Uruguay and the United States. To look beyond averaged frequencies, a latent class analysis (LCA) was conducted to identify possible clusters of school leaders with distinct usage patterns of ICT for leadership and management activities. Findings The results indicate that, in general, German principals use ICT for leadership and management activities on a similar level as their international colleagues. However, they seem to communicate with education authorities significantly more often than their international colleagues, whereas representative activities (presentations, home page) are rather infrequent. The qualitative data point to significant barriers to fully harnessing the potential of using ICT for leadership, management and school improvement such as lack of competencies and lack of adequate support. Originality/value To the best of the authors’ knowledge, this is the first study that focuses on school leadership and management activities using ICT with such a data set. The results provide insights into how German principals use ICT to lead and manage their schools compared to their international counterparts. The qualitative data offers additional insights into possible reasons hindering a more effective use of ICT.
Keywords: Organizational Behavior and Human Resource Management; Education; Organizational Behavior and Human Resource Management; Education

Implementierung schulischer Medienkonzepte als Kooperationsanlass - Schulze, Johanna; Drossel, Kerstin; Eickelmann, Birgit (MedienPädagogik: Zeitschrift für Theorie und Praxis der Medienbildung)
In dem Beitrag wird vor dem Hintergrund der Transformationsprozesse der Digitalisierung und der damit einhergehenden Anforderungen an die institutionsübergreifende Zusammenarbeit zwischen Einzelschulen und dem Unterstützungssystem der Kompetenzteams der Medienberatung NRW als exemplarische Form der Kooperation zwischen Einzelschulen und Bildungsadministration analysiert. Entlang des Implementierungsprozesses schulischer Medienkonzepte, welche als zentrale Schulentwicklungsinstrumente für die Umsetzung digitalisierungsbezogener Schulentwicklungsprozesse gelten, wird mithilfe eines längsschnittlichen Fallstudiendesigns und eines Mixed-Methods-Ansatzes den Fragen nachgegangen, welche Gestaltungsformen sich in der Zusammenarbeit zeigen und welche Gelingensbedingungen und Herausforderungen diesem Prozess zugrunde liegen. Der Beitrag fasst die zentralen Untersuchungsergebnisse zusammen und leitet mögliche Implikationen für die Praxis ab.
Keywords: Pharmacology

Manifold turnpikes, trims, and symmetries - Faulwasser, Timm; Flaßkamp, Kathrin; Ober-Blöbaum, Sina; Schaller, Manuel; Worthmann, Karl (Mathematics of Control, Signals, and Systems)

Computer- und informationsbezogene Kompetenzen und Computational Thinking: Ein Überblick über die Konstrukte der International Computer and Information Literacy Study (ICILS 2018) - Gerick, J.; Eickelmann, Birgit (Kompetenzmodelle für den Digitalen Wandel. Kompetenzmanagement in Organisationen)

Good practice toolkit for improving practice and policies (DigiGen-working paper). - Roth, M. M.; Holmarsdottir, H. B.; Labusch, Amelie; Eickelmann, Birgit; Parsanoglou, D.

Implementierung schulischer Medienkonzepte als Kooperationsanlass. Eine multiperspektivische Betrachtung zu Kooperationsprozessen zwischen Schulen der Sekundarstufe I und dem Unterstützungssystem der Medienberatung NRW - Schulze, Johanna; Drossel, Kerstin; Eickelmann, Birgit (MedienPädagogik 49 (Schulentwicklung))

DigiBody - Digitale Prozesskette zur Abbildung und Optimierung der Fügetechnik im Rohbau - Jamei, Said; Döller, Norbert; Lossau, Sebastian; Beule, Felix; Al Trjman, Mohamad; Aubel, Tobias; Meschut, Gerson; Sommer, Daniel; Facciotto, Silvio; Droste, Alexander; Haufe, Andre; Helbig, Martin; et al. (22. Kolloquium: Gemeinsame Forschung in der Klebtechnik)